2019
DOI: 10.1111/1460-6984.12454
|View full text |Cite
|
Sign up to set email alerts
|

The joint effects of bilingualism, DLD and item frequency on children's lexical‐retrieval performance

Abstract: Background Bilingual children and children diagnosed with developmental language disorder (DLD) are characterized by reduced lexical‐retrieval abilities. Few studies examined their joint contribution and the mechanisms underlying these effects in the lexical domain. Aims To explore the joint effects of bilingualism and DLD by adopting a four‐group comparison in which the difference between bi‐ and monolingual children with DLD is directly compared with that of bi‐ and monolingual children with typical language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 50 publications
3
15
0
Order By: Relevance
“…Note that Russian and Hebrew are similar in the language-specific property of referential choice, i.e., the use of overt and null pronouns. The findings of these two studies are in accord with previous research on bilingual children with special needs, e.g., Developmental Language Disorders (DLD, previously referred to as Specific Language Impairment (SLI)) (e.g., Bird, Genesee & Verhoeven, 2016;Blom & Boerma, 2017;Degani, Kreiser & Novogrodsky, 2019;Meir, 2017;Zebib, Tuller, Hamann, Abed Ibrahim & Prévost, 2020). These studies found no detrimental effect of bilingualism on language development in children with developmental disorders.…”
Section: Introductionsupporting
confidence: 87%
“…Note that Russian and Hebrew are similar in the language-specific property of referential choice, i.e., the use of overt and null pronouns. The findings of these two studies are in accord with previous research on bilingual children with special needs, e.g., Developmental Language Disorders (DLD, previously referred to as Specific Language Impairment (SLI)) (e.g., Bird, Genesee & Verhoeven, 2016;Blom & Boerma, 2017;Degani, Kreiser & Novogrodsky, 2019;Meir, 2017;Zebib, Tuller, Hamann, Abed Ibrahim & Prévost, 2020). These studies found no detrimental effect of bilingualism on language development in children with developmental disorders.…”
Section: Introductionsupporting
confidence: 87%
“…With respect to lexical retrieval, both children with DLD and bilingual children are expected to show difficulties in lexical retrieval. Further, based on the results of Degani et al (2019) utilizing a similar four-group design, we expect that bilingualism would not exaggerate the difficulty in lexical retrieval stemming from DLD. Thus, main effects of bilingualism and of DLD are predicted.…”
Section: Word Learning and Lexical Retrievalmentioning
confidence: 99%
“…Picture naming tasks have been used to explore accuracy and error types for bilingual children with and without DLD. TD bilingual children (e.g., Gross, Buac, & Kaushanskaya, 2014) and their peers with DLD (Degani, Kreiser, & Novogrodsky, 2019) have poorer accuracy on a variety of single-word picture-naming naming tasks in comparison to TD monolingual children. Monolingual children with DLD produce more and a greater variety of error types than their TD peers, including more semantic (Lahey & Edwards, 1999;McGregor, 1997) and phonological errors (Lahey & Edwards, 1999;Sheng & McGregor, 2010).…”
Section: Error Production Patterns For Children With and Without Dldmentioning
confidence: 99%